2022
DOI: 10.21203/rs.3.rs-1305483/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SHED-derived Exosomes Ameliorate Hyposalivation Caused by Sjögren Syndrome via Akt/GSK-3β/Slug-mediated ZO-1 Expression

Abstract: Objective: To explore the therapeutic role and mechanism of exosomes obtained from the supernatant of stem cells derived from human exfoliated deciduous teeth (SHED-exos) in sialadenitis caused by Sjögren syndrome (SS).Methods: SHED-exos were administered to the submandibular glands (SMGs) of 14-week-old nonobese diabetic (NOD) mice, an animal model of the clinical phase of SS, by local injection or intraductal infusion. The saliva flow rate was measured after pilocarpine intraperitoneal injection in 21-week-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…They also expressed the exosome markers CD9, CD63 and heat shock protein 70 (HSP70) (Figure 1c). These results were in keeping with our recent findings (Du et al., 2023). The stimulated saliva flow rate was decreased in 21‐week‐old NOD mice compared with that in 7‐week‐old NOD mice (Figure 1d).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…They also expressed the exosome markers CD9, CD63 and heat shock protein 70 (HSP70) (Figure 1c). These results were in keeping with our recent findings (Du et al., 2023). The stimulated saliva flow rate was decreased in 21‐week‐old NOD mice compared with that in 7‐week‐old NOD mice (Figure 1d).…”
Section: Resultssupporting
confidence: 94%
“…Previously, we reported that SHEDs protected glandular tissues, thereby avoiding immune damage (Du et al., 2019). Recently, we further proved that SHED‐exos can increase the secretory function of surviving glandular epithelial cells (Du et al., 2023). However, whether SHED‐exos can decrease the cell death of SGECs induced by inflammation and then promote secretion is unknown.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations